Riba Dalam Pandangan Alquran Hadis Dan Perspektif Ulama - Septiandy, Mhd Dimas; Hamim, Nabila; Hanafiah, Fahri Luthfi; Lesmana, Angga; Amelia, Rizqa (LPPM Universitas Labuhanbatu, 2023)
The modern economic system implemented in conventional banks contains many elements that are not allowed in islam, one of which is riba. In the implementation of transaction activities in conventional banks there are several things that contain elements of usury such as in bank interest. In the Qur'an riba is explained in several surahs, some of which are on Q.S Ar-Rum/30:39, An-Nisa/4:161, Ali Imran/3: 130, Q.S Al-Baqarah/2: 278-279, and so forth. There is also a hadith of the Prophet that supports the validity of rib aini, as well as the opinions of scholars and fuqaha that increase confidence in the Prohibition of riba. This study uses qualitative methods with a literature interview approach that aims to enable researchers to clearly describe the views of scholars, the Koran and the Hadith against the concept of riba.